Nutritional, Functional, Physical, and Microstructural Properties of Ethiopian Emmer Wheat (Triticum dicoccum L.) Varieties as Affected by Growing Seasons and Grain Types (Hulled and Dehulled) - Bethlehem Melese; Neela Satheesh; Solomon Workneh Fanta; Zewdie Bishaw (Journal of Food Quality)
This study was conducted to evaluate the effect of the growing seasons, grain types, and varieties on physical, proximate, functional, mineral, vitamins, amino acids, and microstructural properties of Ethiopian emmer wheat. One local landrace and three improved emmer wheat varieties (Hydroo, Sinana 01, and Lameso) grown during Meher and Belg seasons and grain types (hulled and dehulled) were used for analysis. The study showed that dehulled Sinana 01 variety from Belg season had the highest (17.82%) protein content. Varieties grown in Belg season showed the highest mineral compositions. The essential amino acids in emmer wheat were higher in the hulled grain type grown in Meher season. The highest vitamin B1 (0.17 mg/g), B2 (0.35 mg/g), and B6 (5.52 mg/g) contents were observed in hulled emmer wheat types grown in Meher season. The study concluded that seasonal variation, grain types, and varieties have a great effect on the proximate, physical, and functional properties of emmer wheat cultivated in Ethiopia.